MANAGEMENT OF PARENTING ACTIVITIES IN PAUD IN MOTIVATING TO BE A WISE PARENT IN THE DIGITAL ERA - Nita Supartini; Arifah A. Riyanto; Kuswandy A. Marfu; Sri Nurhayati (IKIP Siliwangi Bandung, 2020)
The rapid progress of Information and Communication Technology (ICT) accompanied by easy access to social media, especially by minors who are easily exposed to information that has a negative impact on the character of children. Therefore, the involvement of parents is very helpful for teachers to carry out the process of educating children, especially educating children when at home (Parenting).Parenting really determines the growth and development of children's character according to the concept of